Goalkeepers` plasticity during learning of a whole-body visuomotor rotation in a stable or variable environment - Vouras, I.; Chatzinikolaou, K.; Sotirakis, C.; Metaxas, T.; Hatzitaki, V. (European Journal of Sport Science, 2023)
Postural adjustments performed in anticipation of uncertain visual events is a common sensorimotor control problem in open sport skills. In this study, we examined how expert soccer goalkeepers and non-athletes learn a whole body visuomotor rotation during postural tracking of constant and variable visual target motions. Twenty-one (21) soccer goalkeepers (18 ± 15 years, 75 ± 12 kg) and 25 age-matched non-athletes (18 ± 12 years, 75 ± 15 kg) practiced lateral weight shifting on a dual force platform while tracking the motion of a constant (11 goalkeepers and 12 non-athletes) or a variable (10 goalkeepers and 13 non-athletes) visual target with provision of online visual feedback (VF). After 40s of tracking (baseline), the visual presentation of the VF signal reversed direction relative to the participant`s motion (180° visuo-motor rotation) for 60s (adaptation) and then returned to its veridical direction for another 20s (washout). During adaptation, goalkeepers reduced the spatiotemporal error to baseline levels at an earlier time block (3rd block) compared to non-athletes (6th block), but this difference was significant only for groups tracking of the constant and not the variable target motion. Only the groups tracking the constant target increased the spatiotemporal error during the 1st washout block demonstrating a significant aftereffect. It is concluded that goalkeepers adapt faster to the feedback rotation due to their prior field knowledge of relevant visuomotor transformations in anticipation of deceptive visual cues. This expertise advantage however is present only in a stable visual environment possibly because learning is compromised when tracking uncertain motion cues requiring closed loop control.